Diseño y construcción de un prototipo de pasteurizadora para el procesamiento de 50 litros de leche/hora - Tipán Quise, Mery Lucero (2018)
In Ecuador, data from the Agricultural Census of 2000 indicate that 90% of the main dairy processing industries are located in the Sierra and are mainly engaged in the production of pasteurized milk, cheese and milk cream, occupying a secondary plane the other dairy derivatives [1]. In the present project a semi-automated kettle for the pasteurization of raw milk was designed and built for the Campo Verde de Turucucho Association located northeast of the Cayambe canton. According to the magazine EL PAÍS [2], the Campo Verde Association of Turucucho groups 49 families and collects some 1,700 to 2,200 liters of milk per day; Something more in the milking of the morning than in the afternoon. For the dimensioning of the prototype it is proposed to heat a volume of 50lt of milk for the Collection Center, for which we must take some considerations. The starting temperature of raw milk (4 ° C), the height in Cayambe is 2,830 meters above sea level and the working pressure is 14.9 PSI. The equipment allows the pasteurization of raw milk to later manufacture its own derived products such as cheeses, yogurt and milk cream in such a way that they promote the development of the community. Finally, the results obtained will allow to demonstrate in a practical and concrete way, with a scientific basis, how milk and some of its derivatives are processed until reaching the final consumer's palate.